Lower waist circumference in mildly-stunted adolescents is associated with elevated insulin concentration - Ana Paula Grotti Clemente; Carla Danusa da Luz Santos; Vinicius J.B. Martins; Maria Paula Albuquerque; Mariana B. Fachim; Ana Lydia Sawaya (Elsevier, 2014)
Objective: Augmented waist circumference (WC) is associated with non-communicable diseases and could represent a valuable marker in screening for metabolic dysfunctions in subjects with insufficient linear growth. The objective of the present study was to determine whether bio-chemical and hemodynamic parameters and waist circumference vary between mildly-stunted and non-stunted adolescents from impoverished communities of São Paulo, Brazil. Methods: The cross-sectional study involved 206 subjects, aged between 9 and 19 years and living in impoverished areas of São Paulo, Brazil. The sample population was divided according to height-for-age Z-score (HAZ) into stunted (−1 > HAZ ≥ −2) and non-stunted (HAZ ≥ −1) groups, and was sub-divided according to gender. Logistic regression analysis was employed to compare individuals with elevated (> 75th percentile) insulin concentrations. The receiver operating characteristic curves were constructed to determine WC cut-off points that could be used to identify stunted and non-stunted individuals with elevated insulin concentrations. Results: WC cut-off points of 58.25 cm and 67.2 cm allowed for correct classification of 90.7% of stunted and 88.7% of non-stunted individuals in the studied population. While the sensitivity of the model was high for stunted and non-stunted subjects (98.8% and 97.2%, respectively), the specificity was modest (57.1% and 41.2%, respectively). Conclusion: The results presented herein suggest that an increase in plasma insulin is one of the primary metabolic modifications in stunted individuals, and that this alteration could be identified at a lower WC cut-off point than in non-stunted counterparts.